Should we welcome multinational companies' involvement in programmes to improve child health?. (17th June 2015) - Berry, Simon; Berry, Jane; Ramchandani, Rohit; Spencer, Nick
Abstract : Pragmatic partnerships with industry can work argue Simon Berry and colleagues, but Nick Spencer thinks the conflicts of interest are too great